2010
DOI: 10.1097/acm.0b013e3181e2cf2b
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Studies of Publication Misrepresentation by Applicants to Residency and Fellowship Programs

Abstract: The variance in study results of misrepresentation decreases when uniform inclusion criteria are applied. Caution must be used in directly comparing the results of these studies as originally reported. Program directors should be aware that self-promotion in the authorship list is a common form of misrepresentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…These figures underscore the importance of studying aspects of misconduct by researchers which do not involve the published literature, many of which have been largely ignored in non-medical fields. For example, the 18 studies on publication misrepresentation by medical residency and fellowship applicants (Wiggins 2010) stand in contrast to the complete lack of similar studies among post-doctoral applicants. Further studies characterizing various forms of professional misconduct outside of medicine would clarify whether they are more prevalent in medicine than other scholarly fields, and reveal the impacts of all forms of professional misconduct on science as a whole.…”
Section: Postdoc-36mentioning
confidence: 81%
See 1 more Smart Citation
“…These figures underscore the importance of studying aspects of misconduct by researchers which do not involve the published literature, many of which have been largely ignored in non-medical fields. For example, the 18 studies on publication misrepresentation by medical residency and fellowship applicants (Wiggins 2010) stand in contrast to the complete lack of similar studies among post-doctoral applicants. Further studies characterizing various forms of professional misconduct outside of medicine would clarify whether they are more prevalent in medicine than other scholarly fields, and reveal the impacts of all forms of professional misconduct on science as a whole.…”
Section: Postdoc-36mentioning
confidence: 81%
“…• More than 1/3 of ORI's findings of misconduct cases involved misrepresentation of data in grant applications; and ''padding'' of credentials in fellowship applications by medical students is well-documented (Wiggins 2010). Since they may contain information that is manipulated for self-promotion, publication lists and preliminary data presented in applications for grants and professional positions should be subject to the same level of scrutiny as manuscripts under review.…”
Section: Discussionmentioning
confidence: 99%
“…This surprising result attracted much deserved attention from residency and fellowship program directors, as well as others involved in postgraduate medical education. In a meta-analysis of 18 studies that followed, Wiggins 2 found reports that ranged widely from misrepresentations found for 1.8% to 50% of applicants listing publications and for 0.8% to 16.1% of the total number of applicants. The most recently published study, concerning obstetrics and gynecology applicants, found that 25.5% of applicants listing peer-reviewed articles or abstracts committed ''major errors,'' while 24.1% had articles or abstracts that were unverified.…”
mentioning
confidence: 99%
“…2 This can be accomplished by eliminating unlocated journals for which the accuracy of publication record cannot be verified, as-of-yet unpublished ''in press'' articles, and typographic errors from the counts of misrepresentation. Using these criteria, Wiggins 2 found that no particular study characteristic, including sample size, the percentage of applicants with publications, and the number of data sources, was found to correlate with the percentage of misrepresentation discovered.…”
mentioning
confidence: 99%
See 1 more Smart Citation